Perfil, sobrecarga e qualidade de vida de cuidadores de idosos atendidos em ambulatório de geriatria e neurogeriatria - Fornazari, Bruna Aparecida (2018)
The increases due to population aging, the prevalence of chronic-degenerative diseases increases significantly and, among these, dementia stands out as a risk factor for disability and functional loss, which implies constant care that reverts in compromising quality of life and burnout to informal caregivers. Objectives: To characterize the profile of the informal caregivers of the elderly attend geriatrics and psycho-geriatrics outpatient clinics and to evaluate the quality of life related to health and burnout. Methods: This is a descriptive / cross-sectional study. Participants included 60 informal caregivers of elderly men and women, aged between 25 and 84 years who care for the elderly between 60 and 85 years, with chronic diseases and accompanied them in the outpatient care of Geriatrics and Psycho-geriatrics. The following materials were used to collect: Socio-Demographic Questionnaire; Quality of Life Questionnaire SF36 and Zarit Burden Interview Scale. Participants were invited to participate in the study after confirming that they were informal caregivers of the elderly, that is, they perform non-professional care. Results: Of the total number of participants, the predominance of women (80%), with a mean age of 54.93 years, was ± 14.6, married (66.7%), active at work (38.3%), mainly family members, daughters (43.3%), or wives (20%), who live with the elderly (65%), and who attended incomplete primary education (40%). The majority (51.7%) dedicate more than 10 hours a day to care, take care of their family members between 01 to 05 years, do not carpeted with other family members and 86.6% cannot pay someone to help with the care of the elderly. Regarding the overload of care in the present study, 45% and 25% of the caregivers presented moderate and moderate to severe overload, respectively, with a variation from 8 to 74 (mean of 33.06 and dp = 15.86), it was verified in the different analyzed dimensions of SF-36, with the lowest results being general health status and social aspects. Conclusion: The results reinforce the existence of a relationship between caregiver burnout and quality of life impairment, therefore, it is necessary to invest in public health policies that act directly to minimize the effects of burnout and quality of life of this population, optimization of care network and health services.